Kesenjangan Penghasilan antar Gender di Indonesia Tahun 2013 dengan Metode Dekomposisi Blinder-Oaxaca - Mardiana Mardiana (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2015)
This research aims to find out the gender earnings gap using Blinder-Oaxaca decomposition method. This method divides the causes of the gender earnings gap into endowment factor which is explained by age, education, residence, working hours, activity status, occupation and industry, as well as discrimination factor. Probit work participation did before estimate earnings by gender to eliminate bias in the sample selection. Using Sakernas August 2013, it is found that the gender earnings gap is 47,29 persentage point. Discrimination factor contribution is bigger than endowment factor in explaining the gender earnings gap in Indonesia. The contribution of discrimination factor is 41,40 percentage point (87,53 percent), while endowment factor contribution is 5,9 percentage point (12,47 percent).